The use of drug eluting stents in single and multivessel disease: results from a single centre experience. Issue 9 (13th August 2004) - Mikhail, G W; Airoldi, F; Tavano, D; Chieffo, A; Rogacka, R; Carlino, M; Montorfano, M; Sangiorgi, G; Corvaja, N; Michev, I; Orlic, D; Di Mario, C; et al.
Abstract : Objective: Drug eluting stents have been shown to reduce the rate of in-stent restenosis in cases where single lesions are treated. The performance of these stents, in patients with multivessel disease and complex lesions, however, remains unknown. Our experience with sirolimus eluting stents in such patients is presented. Design and patients: This study includes all consecutive patients treated at San Raffaele Hospital and EMO Centro Cuore Columbus, Milan, Italy treated with sirolimus eluting stents. Results: Between April 2002 and March 2003, 486 patients with 1027 lesions were treated (437 males, 49 females) with a mean (SD) age of 62.2 (10.5) years. Of all patients studied, 19.1% had single vessel disease, 33.8% had two vessel disease, and 47.1% had three vessel disease. Of the whole study group, 20.3% of patients had diabetes mellitus. A mean (SD) of 2.3 (0.4) stents per patient and 1.1 (0.2) stents per lesion were implanted. The baseline mean reference diameter was 2.7 (0.6) mm with a mean minimal luminal diameter of 0.9 (0.5) mm. Post-stenting, the acute gain was 1.8 (0.6) mm. During hospital stay one patient died (0.2%) and 13 (2.7%) patients had in-hospital myocardial infarction (MI). One patient required urgent repeat percutaneous coronary intervention. Six months clinical follow up was performed in all 347 eligible patients. Six months mortality was 2.0% (n  =  7) and acute MI occurred in 0.3% (n  =  1). Target lesion revascularisation occurred in 9.5% (n  =  33) of the patients and target vessel revascularisation (TVR) in 11.5% (n  =  40) of the patients. Major adverse cardiac event rate was 13.8% (n  =  48). TVR was 4.5% for single vessel disease and 13.2% for multivessel disease. Diabetes mellitus was the only significant predictor for TVR. Conclusion: The use of drug eluting stents in single and multivessel coronary disease produces good short and medium term results with a low rate of revascularisation. Longer term follow-up is required to confirm these observations.